2018
DOI: 10.1080/13625187.2018.1445850
|View full text |Cite
|
Sign up to set email alerts
|

Dual method use among long-acting reversible contraceptive users

Abstract: Clinicaltrials.gov Identifier NCT01986439.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…The relationship between wealth and LARC use may vary by locality, 16 and our findings support the need for more investigation into this relationship. Our results also support the association between LARC use and inconsistent condom use, 26,27 which emphasizes the importance of dual protection counseling when implementing family planning interventions in countries with a higher HIV incidence.…”
Section: Resultssupporting
confidence: 81%
“…The relationship between wealth and LARC use may vary by locality, 16 and our findings support the need for more investigation into this relationship. Our results also support the association between LARC use and inconsistent condom use, 26,27 which emphasizes the importance of dual protection counseling when implementing family planning interventions in countries with a higher HIV incidence.…”
Section: Resultssupporting
confidence: 81%
“…The prevalence of any condom use in the past 6 months was 28.5% among LARC users and 40.0% among non-LARC contraceptive users in our sample. The Contraceptive CHOICE Project, a convenience sample of women ages 14-45 in St. Louis, reported 32% of LARC users reported condom use in the past 6 months (Bernard et al, 2018). Data from the NSFG showed that rates for condom use among IUD/implant users were low in both the interview month (1.8%) and at last intercourse 15 (1.9%) (Pazol, Kramer, & Hogue, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is concern that individuals may be less likely to use condoms after beginning LARC methods as they may potentially be less worried about unintended pregnancies (Potter & Soren, 2016;Williams & Fortenberry, 2013). Numerous studies on condom use with LARC methods have been conducted among adolescents and young women (Bastow, Sheeder, Guiahi, & Teal, 2018;Steiner, Liddon, Swartzendruber, Rasberry, & Sales, 2016;Thompson et al, 2017;Tyler et al, 2014;Walsh-Buhi & Helmy, 2018) who are disproportionately burdened with STIs and unintended pregnancies, but far fewer studies have been conducted among a broader age range of adults (Bernard, Zhao, & Peipert, 2018;McNicholas, Klugman, Zhao, & Peipert, 2017), especially at the population level. Although women in their late twenties, thirties, and forties have a lower rate of STIs compared to women under 25, their risk is not negligible particularly given the recent annual increases in STIs that affect individuals as well as newborns (i.e., congenital syphilis) (Centers for Disease Control and Prevention, 2019).…”
Section: Dual Larc and Condom Usementioning
confidence: 99%
See 1 more Smart Citation
“…Behaviorally, women who use modern methods of contraception may have different condom use patterns, sexual frequency and numbers of sexual partners as compared to women not using modern contraception. 4 7 Uncontrolled and/or residual confounding due to inaccurate measurement of sexual behavior is a significant concern in evaluating the results of observational studies on the topic – results may be biased toward or away from the null depending on the type and frequency of misreporting or lack of adjustment for salient variables – and studies which randomize women to contraception are lacking. 6 Possible biological mechanisms linking contraceptives and STIs include alteration of the vaginal epithelium, changes in mucus production and in multiple immune responses (eg, production and availability of cytokines, chemokines and relevant cell types in the upper and lower female reproductive tract and alteration of the vaginal microbiota).…”
Section: Introductionmentioning
confidence: 99%